Factors associated with concomitant prostate cancer in benign prostatic hyperplasia patients aged 60 years and above - Mengdi Wu; Kun Zheng; Yanjie Cao; Qiaoxiang Yin; Yue Hu; Qitao Ren; Huijing Zhu; Xiaohua Lan; Weiwei Zhu (The Aging Male)
Objective Prostate hyperplasia and cancer are more prevalent in middle-aged and elderly men. Previous studies have linked both disorders to androgen receptors. Herein, efforts were made to identify factors associated with prostate cancer in patients ≥60 years, aiming to enhance their health management.Methods An analytical framework was established utilizing the “Prostate Cancer Early Warning Dataset” from the National Clinical Medical Science Data Center. Variables selection was conducted through LASSO regression, followed by multifactorial logistic stepwise regression to construct a predictive model.Results A total of 1,502 patients with BPH and 294 with combined PCa were hereby included. Multivariate regression delineated several independent predictors of PCa coexistence, including age (OR [95% CI]: 1.06 [1.04–1.09], p < 0.001), fPSA/tPSA ratio (OR [95% CI]: 0.01 [0.002–0.05], p < 0.001), serum inorganic phosphorus (OR [95% CI]: 5.85 [2.61–13.15], p < 0.001), globulin levels (OR [95% CI]: 1.06 [1.02–1.11], p = 0.005), serum potassium (OR [95% CI]: 0.58 [0.40–0.86], p = 0.006), low-density lipoprotein (LDL) cholesterol (OR [95% CI]: 1.28 [1.06–1.54], p = 0.009), among others.Conclusion The analysis revealed connections between PCa occurrence in men aged over 60 and BPH, along with specific serum biomarkers such as inorganic phosphorus, globulin, LDL cholesterol, lower fPSA/tPSA ratios and serum potassium.